ANALISIS PENGARUH TATA KELOLA TI TERHADAP TRANSFORMASI DIGITAL DAN KINERJA ASURANSI B - Cantika Dewi Fortuna; Monica Suryatama Deby; Rahmat Mulyana; Luthfi Ramadani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The emergence of the latest technological disruption, high competition from digital competitors, changes in consumer behavior towards digital, and the COVID19 pandemic have disrupted many incumbent companies and forced them to carry out digital transformation (DT). However, many companies experience DT failure due to poor governance. Previous research has shown the importance of IT governance (ITG) in improving organizational performance (OP). However, the effectiveness of this traditional ITG is doubtful to support DT. Recent studies show the influence of hybrid, traditional, and agile/adaptive governance on DT. However, there is a need further to validate the impact of hybrid ITG on DT and identify the effect of DT on OP. Therefore, research has been carried out using the case study method on bank A which was disrupted by fintech. Data was collected using semi-structured interviews of 11 essential roles related to DT by triangulation of internal bank documents. Whereas the data is processed using thematic analysis. This study succeeded in validating all hybrid ITG mechanisms at bank A, even adding several others, and identifying the influence of the hybrid ITG to DT dimension, and DT dimensions to organizational performance (OP), including their achievements. The research results can be helpful as an implementation reference for practitioners and further deepen similar research or extend it to a different industry.